Measurement of gamma + b + X and gamma + c + X Production Cross Sections in pp > Collisions at s=1.96 TeV - Abazov, V. M.; Abbott, B.; Abolins, M.; Acharya, B. S.; Adams, M.; Adams, T.; Aguilo, E.; Ahsan, M.; Alexeev, G. D.; Alkhazov, G.; Alton, A.; Neal, H. A.; et al. (Amer Physical Soc, 2009)
First measurements of the differential cross sections d(3)sigma/(dp(T)(gamma)dy(gamma)dy(jet)) for the inclusive production of a photon in association with a heavy quark (b, c) jet are presented, covering photon transverse momenta 30 < p(T)(gamma)< 150 GeV, photon rapidities |y(gamma)|< 1.0, jet rapidities |y(jet)|< 0.8, and jet transverse momenta p(T)(jet)> 15 GeV. The results are based on an integrated luminosity of 1 fb(-1) in pp collisions at s=1.96 TeV recorded with the D0 detector at the Fermilab Tevatron Collider. The results are compared with next-to-leading order perturbative QCD predictions.